Bilateral Loudness Balancing and Distorted Spatial Perception in Recipients of Bilateral Cochlear Implants. Issue 5 (September 2015) - Fitzgerald, Matthew B.; Kan, Alan; Goupell, Matthew J.
Abstract : Objective: To determine whether bilateral loudness balancing during mapping of bilateral cochlear implants (CIs) produces fused, punctate, and centered auditory images that facilitate lateralization with stimulation on single-electrode pairs. Design: Adopting procedures similar to those that are practiced clinically, direct stimulation was used to obtain most-comfortable levels ( C levels) in recipients of bilateral CIs. Three pairs of electrodes, located in the base, middle, and apex of the electrode array, were tested. These electrode pairs were loudness-balanced by playing right-left electrode pairs sequentially. In experiment 1, the authors measured the location, number, and compactness of auditory images in 11 participants in a subjective fusion experiment. In experiment 2, the authors measured the location and number of the auditory images while imposing a range of interaural level differences (ILDs) in 13 participants in a lateralization experiment. Six of these participants repeated the mapping process and lateralization experiment over three separate days to determine the variability in the procedure. Results: In approximately 80% of instances, bilateral loudness balancing was achieved from relatively small adjustments to the C levels (⩽3 clinical current units). More important, however, was the observation that in 4 of 11 participants, simultaneous bilateral stimulation regularly elicited percepts that were not fused into a single auditory object. Across all participants, approximately 23% of percepts were not perceived as fused; this contrasts with the 1 to 2% incidence of diplacusis observed with normal-hearing individuals. In addition to the unfused images, the perceived location was often offset from the physical ILD. On the whole, only 45% of percepts presented with an ILD of 0 clinical current units were perceived as fused and heard in the center of the head. Taken together, these results suggest that distortions to the spatial map remain common in bilateral CI recipients even after careful bilateral loudness balancing. Conclusions: The primary conclusion from these experiments is that, even after bilateral loudness balancing, bilateral CI recipients still regularly perceive stimuli that are unfused, offset from the assumed zero ILD, or both. Thus, while current clinical mapping procedures for bilateral CIs are sufficient to enable many of the benefits of bilateral hearing, they may not elicit percepts that are thought to be optimal for sound-source location. As a result, in the absence of new developments in signal processing for CIs, new mapping procedures may need to be developed for bilateral CI recipients to maximize the benefits of bilateral hearing. Abstract : In some individuals, conventional mapping procedures for bilateral CIs do not control the perceived intracranial position of an auditory image. Thus, distortions to the spatial maps may be introduced, hindering sound localization abilities. Here we examined whether systematic bilateral loudness balancing eliminated distorted spatial maps in bilateral CI users. Our data suggest that even after careful loudness balancing, bilateral CI users still regularly perceive images that are suboptimal for sound localization. Thus, while current mapping procedures are sufficient to enable many benefits of bilateral hearing, they may not elicit percepts that are thought to be optimal for sound-source location.